Predicting protein-peptide binding sites with a deep convolutional neural network. (7th July 2020) - Wardah, Wafaa; Dehzangi, Abdollah; Taherzadeh, Ghazaleh; Rashid, Mahmood A.; Khan, M.G.M.; Tsunoda, Tatsuhiko; Sharma, Alok
Graphical abstract: Abstract: Motivation: Interactions between proteins and peptides influence biological functions. Predicting such bio-molecular interactions can lead to faster disease prevention and help in drug discovery. Experimental methods for determining protein-peptide binding sites are costly and time-consuming. Therefore, computational methods have become prevalent. However, existing models show extremely low detection rates of actual peptide binding sites in proteins. To address this problem, we employed a two-stage technique - first, we extracted the relevant features from protein sequences and transformed them into images applying a novel method and then, we applied a convolutional neural network to identify the peptide binding sites in proteins. Results: We found that our approach achieves 67% sensitivity or recall (true positive rate) surpassing existing methods by over 35%.